(untitled) (Research, Society and Development, 2022)
The objective of this work was to evaluate the influence of the addition of carrageenan on the particle size distribution of dulce de leche for confectionery. The experimental design adopted (n=3) was in a 2x3 factorial scheme, as follows: two types of carrageenan (Lactogel FX 6369 and Viscarin BK 7161) in three different concentrations (0.0% m/m, 0.3% m/m 0.5% w/w). Particle size analyzes of the products were performed by laser diffraction in order to identify the influence of the treatments. In the initial step of the process, which was the mixing of the ingredients, it was possible to observe the influence of the carrageenans on the particle size distribution with a reduction in the volumes (%) of the particle populations in the nanometric region of the casein micelles (between 0.04 µm and 0.4 µm) and fat globules (between 1.0 µm and 10 µm), providing the formation of particles in a third (20 µm) and a fourth region (above 40 µm). This displacement of particles to regions of greater diameter suggests the influence of carrageenans even before the heating and evaporation stage. A significant decrease in the volume (%) of particles smaller than 1.0 µm was also observed in products manufactured without the addition of carrageenan, on the same day of manufacture and also after 15, 30 and 45 days of shelf-life. This effect was not observed in products with the addition of carrageenan. These results demonstrate the influence of these thickeners/stabilizers on the maintenance of particles in the nanometric region of casein micelles, directly influencing the formation of the three-dimensional matrix of dulce de leche for confectionery and its technofunctional aspects.